Armazenabilidade de sementes de soja tratadas com inseticidas e sua relação com a temperatura ambiental - Miquicene, Felisberto Venâncio Chicamasso (2020)
Due to the increasing use of industrial seed treatment, for technical and logistical reasons, chemical treatments are, being carried out many times before storage. Another important aspect that needs clarification is the storage relationship of treated seeds and soybean genotypes. It is important that the physiological quality of treated seeds be maintained until sowing, even under different storage temperatures. The objective of this research was to evaluate and monitor the effects of chemical treatments with insecticides on the physiological quality of soybean seeds during storage, depending on the period and condition of the environment. Soybean seeds from two cultivars, M5971IPRO and M6410IPRO, were analyzed separately. The experimental design used was completely randomized in a 5x3x4 factorial arrangement, with five seed treatments, involving insecticides and controls (Avicta®, Cruiser®, Fortenza®, Polymer + water and Absolute Control), three temperatures throughout storage (10; 20 and 30 °C) and four storage periods (0; 50; 100 and 200 days), in four repetitions. The following parameters were evaluated: moisture content, first germination count, germination, seedling emergence, accelerated aging on paper and accelerated aging on soil and sand substrate. The temperature of 30 °C directly affect the quality during storage of seeds treated with insecticides, high temperatures accentuate the degradation of reserves and your sensitivity to treatment. At 10 ℃ storage, the physiological quality of soybean seeds treated with Avicta®, Cruiser® and Fortenza® is preserved for 200 days. The insecticides Avicta®, Cruiser® and Fortenza® and Polymer + water negatively affect the physiological quality of soybean seeds stored after 100 days at 20 and 30 °C temperature. In soybean seeds stored at 30 ℃ there was a reduction in physiological quality regardless of the treatment to which they were submitted. The insecticidal molecules provide different rates of deterioration/susceptibility of soybean seeds and seedlings during storage.